Edible nano-bio-composite film cargo device for food packaging applications. (March 2017) - Basu, Aalok; Kundu, Sonia; Sana, Santanu; Halder, Asim; Abdullah, Md Farooque; Datta, Sriparna; Mukherjee, Arup
Graphical abstract: Highlights: Polylactide nanoparticles non-covalent interactions in chitosan matrix film was studied in depth. Quercetin, a bioflavonoid was used in nanoparticles for functionalization of packaging films. Nanoparticles embedding provided bacteria deterrent surface and superior film properties. Newer nano-bio-composite cargo films expressed superior antioxidant and antimicrobial properties. Abstract: This work is meant to design newer nano-bio-composite films for food packaging applications. Polylactide nanoparticles non-covalent interaction in chitosan matrix was carefully studied and used further to develop uniform nano-bio-composite films. Environmentally benign materials and processes were applied throughout for an intended application in packaging of edibles. Nanoparticles array laden in polysaccharide films served as cargo loaders for active molecules. Quercetin, a bioflavonoid, ubiquitous in many plant species was used as model cargo molecule. Sustained quercetin release imparted a synchronized anti-microbial and antioxidant properties in finished packaging films. Microstructures when examined in FESEM and AFM, suggested nanoparticles homogenous dispersion throughout the film matrix. Film surface RMS roughness in tapping mode AFM experiment was recorded at 1.63 ± 0.23 nm which typically represented conditions for microbial deterrence. Control chitosan film radical scavenging capacity was 5.8% in DPPH assay while that was recorded at 23.5% in new active packaging films.